(untitled) (Journal of Partial Differential Equations, 1989)
In this paper we generalize the comparative method of solving some non-degenerate reaction-diffusion systems to a class of nonlinear degenerate parabolic systems without quasi-monotony, and obtain the relevant theorem of upper-lower solutions.